Morphological alterations in skeletal muscle of spontaneously hyperensive rats - Hernández, Noelina; Torres, Sonia H.; Losada, Mercedes; Finol, Héctor J. (Investigación Clínica, 2013)
Â The Extensor digitorum longus (EDL) and the soleus museles of spontaneously hypetensive rats (SHR) were studied in comparison with those of their normal counterparts, the Wistar Kyoto (WKY) rats. Quantitative assessment of capillaries and fibre typing was done with optical microscopy, while the study of capillary abnormalities was performed by ultrastructural observation. There were no differences in fibre type proportion or in capillarity indexes between the SHR and the control rats. A reduction in the area of IIB fibres was found in the EDL muscle of the hypertensive animals. The ultrastructural study showed abnormalities in the capillaries of both muscles in SHR, the cross section of the endothelial cells was enlarged; there was irregular distribution of caveolae and pinocytic vesicles, the capillary base ment membrane showed irregular width, with parts en grossed and reduplicated. Some pericytes were prominent. There were macrophages present in the interstitial space. In some muscle fibres there was disorganization of the sarcomere structure, swelling of the sarcotubular system, abundant autophagic vacuoles, and proliferative satellite cells. There were abundant collagen fibrils. The presence of cellular rests, autophagic vacuoles and loss of sarcolemma indicated necrosis. It can be concluded, that in SHR, muscle capillaries showed alterations that may be the substrate of functional rarefaction, although anatomical rarefaction (number reduction) could not bedemon strated. In EDL and soleus muscles of SHR, signs of a mild myopathy with focal fibrosis were present.